Effect of p-GaN layer on the properties of InGaN/GaN green light-emitting diodes. Issue 4 (13th February 2015) - Wang, Wenliang; Liu, Zuolian; Zhou, Shizhong; Yang, Weijia; Lin, Yunhao; Wang, Haiyan; Lin, Zhiting; Qian, Huirong; Li, Guoqiang
Abstract: Abstract : InGaN/GaN green light-emitting diodes (LEDs) have been prepared by metal-organic chemical vapor deposition with various growth temperatures for p-GaN layer. The structural and optoelectronic properties of as-grown multiple quantum wells (MQWs) and LEDs are studied in detail. It reveals that with the growth of p-GaN layer, the crystalline qualities of the as-grown n-GaN layer are improved significantly, while the optoelectronic properties of MQWs are decreased dramatically. Furthermore, the mechanisms for the effect of p-GaN growth temperature on the properties of InGaN/GaN green LEDs are proposed. It is demonstrated that the p-GaN layer grown at a suitable temperature of 950 °C shows the highest optoelectronic properties due to the fact that this suitable temperature for p-layer growth is good for the Mg doping and would not cause the fluctuation of indium in the MQWs, and eventually benefits to the effective recombination of carriers. This work provides an optimized p-GaN layer growth temperature for realizing highly efficient InGaN/GaN green LED devices.